(untitled) (Biological Sciences - PJSIR, 2009)
Candidiasis and systemic mycosis due to opportunistic pathogens is frequently reported in Sindh, especially in rural areas. In search of local antifungal medicinal plants, methanol, petroleum ether and aqueous extracts of five native medicinal plants Trachyspermum ammi, Hyoscyamus niger, Carum roxburgianum, Linum usitatissimum and Centella asiatica were screened against five Candida strains including three strains of Candida albicans and one strain of C. glabrata and C. tropicalis, each. Antimicrobial screening of five filamentous fungal strains of clinical origin comprising of three strains of Aspergillus niger, one species of A. flavus and Penicillium each, revealed 100% activity of methanolic extract of ammi; petroleum ether extract of T. ammi and H. niger and methanolic extracts of H. niger, C. asiatica and C. roxburgianum produced 60, 20, 50, 50 and 10% inhibition, respectively, whereas, L. usitatissimum was inactive. Reference antibiotics were Nystatin and Amphotericin-B for yeast species and filamentous fungi, respectively. Least minimum inhibitory concentration (125 mg/disc) against Candida sp. was produced by the methanolic extract of T. ammi and H. niger and 500 and 1000 mg/disc against Aspergillus species, respectively. Results indicated that T. ammi and H. niger may be considered as potential future antifungal agents.